ANÁLISIS FINANCIERO EN LA COOPERATIVA DE AHORRO Y CRÉDITO UNIÓN Y PROGRESO UNIPRO LTDA. DE LA CIUDAD DE LOJA. PERIODOS 2015-2016 - Lazo Bermeo, Joel Adrian (2018)
The thesis work entitled: FINANCIAL ANALYSIS IN THE COOPERATIVE OF SAVINGS AND CREDIT UNIÓN Y PROGRESO UNIPRO LTDA. FROM THE CITY OF LOJA. PERIODS 2015-2016, addressed to evaluate the economic and financial position of the cooperative, allowing a diagnosis on the real state of the cooperative and thus issue a financial report to improve the economic and financial situation. The vertical analysis to the Financial Statements of the Savings and Credit Cooperative was elaborated, which allowed to know the degree of participation of the accounts with respect to the group that they belong, determined that the assets the credit portfolio is the most representative account with a 80.79% in the year 2015 and 66.15% for the year 2016; while liabilities include public obligations with 75.86% in 2015 and 76.21% for 2016; the equity is adequate to support your current and future operations; Finally, of the total income, the interest and discounts of the loan portfolio represent 74.38% in 2015 and 72.96% in the 2016 period. In addition, the horizontal analysis was carried out that allowed identifying the variations that have occurred in a period with respect to another, determining a decrease in credit portfolio of 14.86%; the obligations with the public increased 4.46%; equity increased by 15.04% and revenues, as well as expenses, decreased by 10.13% and 2.75% respectively. Subsequently, financial indicators established by the Superintendence of Popular and Solidarity Economy were applied, which helped to deepen the 5 information regarding: Patrimonial Sufficiency that moderately supports immobilized assets; the delinquency rate decreased by 12%, reflecting the recovery of delinquent loans; the financial intermediation process shows a decrease of 21.88%, indicating that there was a decrease in the placement of loans, in terms of liquidity, an increase of 26.42%, reflecting that the entity has the capacity to respond to immediate cash requirements. Finally, a financial report was prepared in order that managers and administrators know the results of the analysis and the real situation of the cooperative, considering the conclusions and recommendations in order to help in the correct decision making. After applying the financial analysis the most relevant conclusion is that the Cooperative is not generating the appropriate profitability, since in 2016 it was 0.22%, evidencing that the income is not enough to strengthen the equity, since when applying The indicator of Financial Intermediation in 2016 was 81.66%, which indicates that the resources received by the partners are not being efficiently placed in loans.